PENGEMBANGAN BISNIS LOKAL BERBASIS KOMUNITAS MELALUI COACHING DAN MENTORING DI PPA AGAPE DESA NGUNUT - TULUNGAGUNG - Sahetapy, Wilma Laura; Suprapto, Widjojo; Harjanti, Dhyah; Pratama, Vicky Alvindra; Divanata, Marcellino Darren; Jhesica, Josephin; Palumian, Yonathan (Jurnal Padamu Negeri, 2025)
Agape Child Development Center (PPA Agape) is an institution focused on holistic child development aimed at liberating children from poverty. To support this mission, PPA Agape endeavors to open several business units run by workers and children sponsored by PPA Agape. The businesses run by PPA Agape include Etawa goat farming, selling fruits grown on PPA Agape's land, and a beauty and self-care store. Some problems faced by these small business units include low product awareness, limited marketing, and a lack of product variety. This community service activity aims to develop initial or simple strategies related to product marketing of the business units so that they become better known to a broader audience. The activities and support conducted at PPA Agape include business coaching and mentoring for PPA children aged 12 and above to provide insights on the importance of entrepreneurship, creating a Tokopedia account as an online sales platform for the beauty salon products, and creating an Instagram account as a promotional platform for the beauty salon products run by PPA Agape.